The Experiential Leadership Ecosystem: A New Model for Student Leadership Development in Islamic Boarding Schools - Na'im, Zaedun; Abidin, Munirul; Walid, Muhammad (JURNAL AL-TANZIM, 2026)
This study aims to analyze leadership development strategies among students in Islamic boarding schools (pesantren) and to conceptualize these strategies into an integrated model. This study uses a qualitative, single-case design. Data were collected through in-depth interviews with fifteen purposively selected informants, participant observation, and analysis of organizational documentation and activity reports. Data analysis was conducted through data condensation, data presentation, and conclusion drawing and verification. The results show that student leadership development is carried out through a four-level cyclical strategy: basic learning through daily routines and role models; active involvement in internal student organizations; delegation of roles to represent the pesantren in external forums; and devolution of authority to senior students for managing strategic affairs. The main finding of this study is the conceptualization of these strategies within the “Experiential Leadership Ecosystem” model, which maps the process of student leadership development into four hierarchical, iterative levels of authority. This model integrates modern leadership theory with typical Islamic boarding school leadership practices. The research indicates that effective leadership development requires authentic participatory structures, integrating leadership learning into daily activities, and strengthening a culture of trust and mentoring among caregivers, teachers, and students.